Wildlife forensic investigation : principles and practice - Cooper, J. E. (John Eric), 1944-; Cooper, Margaret E. (Boca Raton : CRC Press, 2013)
'Providing an in-depth introduction to the rapidly evolving field of wildlife forensics, this volume first chronicles the history of wildlife conservation and environmental protection with an emphasis on its global importance in the 21st century. It then explains and discusses the crucial role of wildlife forensics in terms of investigating contraventions of national, regional and international legislation. The text focuses on wildlife forensic science as it relates to animals but also addresses plants and habitats because of their relevance to the conservation of animals. It also covers environmental monitoring and working with both dead and live animals. Covers the entire investigative process of wildlife forensics. Describes the personnel and agencies involved in wildlife investigation. Discusses the investigation of both live and dead animals. Includes international case studies. Offers appendices for equipment, useful document templates, specimen forms and other sources of information'--
Includes bibliographical references : pages 655-722 and index.
Keywords: Veterinary forensic medicine; Veterinary pathology; Environmental monitoring -- International cooperation; Wildlife conservation -- International cooperation; Wildlife conservation -- Law and legislation